Policies and Research in Identity Management Third IFIP WG 11.6 Working Conference, IDMAN 2013, London, UK, April 8-9, 2013. Proceedings - Fischer-Hübner, Simone; Leeuw, Elisabeth de.; Mitchell, Chris (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Third IFIP WG 11.6 Working Conference on Policies and Research in Identity Management, IDMAN 2013, held in London, UK, in April 2013. The 6 refereed full and 4 short papers presented together with 3 short position papers and a keynote paper were selected from 26 submissions. The papers have been organized into topical sections on privacy and identity management, anonymous credentials, authentication and access control, risk management of identity management, identity management with smart cards, and federated identity management.
Towards Practical Attribute-Based Identity Management: The IRMA -- Data Protection by Default in Identity-Related Applications -- Privacy-Friendly Checking of Remote Token Blacklists -- Concepts and Languages for Privacy-Preserving Attribute-Based Authentication -- Efficient Selective Disclosure on Smart Cards Using Idemix -- Identity Management and Integrity Protection in Publish-Subscribe Systems.-Extended HTTP Digest Access Authentication -- Executable Model-Based Risk Assessment Method for Identity Management Systems -- Privacy Risk Analysis is about Understanding Conflicting Incentives -- Risk Analysis of Identity Management Approaches Employing Privacy Protection Goals -- The Radboud Reader: A Minimal Trusted Smartcard Reader for Securing Online Transactions -- Extending EMV Payment Smart Cards with Biometric On-Card Verification -- Dynamic Identity Federation Using Security Assertion Markup Language (SAML) -- Logout in Single Sign-on Systems.
SpringerLink eBooks.
Keywords: Computer science; Special purpose computers; Computer security; Data encryption (Computer science).; Biometrics (Biology).; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Biometrics; Special Purpose and Application-Based Systems; Management of Computing and Information Systems; Software engineering; Data protection; Biometrics; Information Systems